IMPLEMENTATION OF MANDATORY REPORTING INSTITUTIONS (IPWL) AT THE SPECIAL UPTD RSJ PROF. DR. MUHAMMAD ILDREM NORTH SUMATRA PROVINCE - Dian Sukmawarni Siregar; Nina Siti Salmaniah Siregar; Rudi Salam Sinaga (International Journal of Cultural and Social Science, 2026)
This study aims to analyze the implementation of the Mandatory Reporting Recipient Institution (IPWL) at UPTD Khusus RSJ Prof. Dr. Muhammad Ildrem, North Sumatra Province, and to identify the inhibiting factors in its implementation. The IPWL program is mandated by Law Number 35 of 2009 concerning Narcotics and Government Regulation Number 25 of 2011, which emphasize a rehabilitative approach for drug addicts and victims of drug abuse. This research employs a qualitative method using interviews, observation, and documentation as data collection techniques. The informants consist of the hospital director, medical staff, nurses, counselors, and IPWL residents. The analysis applies Edward III’s policy implementation theory, which includes four key variables: communication, resources, disposition of implementers, and bureaucratic structure. The findings indicate that the implementation of IPWL at UPTD Khusus RSJ Prof. Dr. Muhammad Ildrem has been conducted in accordance with established standard operating procedures, particularly in medical and psychosocial rehabilitation services. However, several challenges remain, including limited human resources, inadequate public socialization, negative societal stigma toward drug users, and budget constraints. The study concludes that the success of IPWL implementation is strongly influenced by effective policy communication, adequate resources, implementers’ commitment, and supportive bureaucratic structures. Therefore, enhanced public awareness campaigns, institutional capacity strengthening, and sustained policy support are necessary to improve the effectiveness of narcotics rehabilitation programs in North Sumatra Province.